2012
DOI: 10.1016/j.math.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of duration and amplitude of spinal manipulative therapy (SMT) on spinal stiffness

Abstract: The aim of this study was to determine the effect of spinal manipulation therapy (SMT) force magnitude and force duration on the spinal stiffness of a feline preparation. A mechanical device performed simulated SMTs at the L6 spinous process in 22 anesthetised felines. Subjects were divided into four groups. Two groups (no preload, preload) received SMT having maximal displacements of 1.0mm, 2.0mm and 3.0mm of total displacement (displacement control). In two other groups (preload, no preload), SMTs were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 34 publications
1
41
1
Order By: Relevance
“…Because the thrust of an HVLA-SM is intended to impart movement to a vertebra (Bergmann, 2005) we first applied a preload force beyond which the L 6 vertebra would be expected to move during the thrust using methods previously described (Vaillant et al, 2012; Reed et al, 2013; Cao et al, 2013). Thrust duration was fixed at 100ms based upon clinical findings (Hessell et al, 1990; Herzog et al, 1993; Triano, 2001) where thrust durations in the thoracic and lumbar spines are typically less than 150ms and upon animal studies (Pickar and Kang, 2006; Pickar et al, 2007; Reed et al, 2013) where 100ms represents the threshold duration at which a non-linear increase in muscle spindle discharge occurred.…”
Section: Muscle Spindle Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Because the thrust of an HVLA-SM is intended to impart movement to a vertebra (Bergmann, 2005) we first applied a preload force beyond which the L 6 vertebra would be expected to move during the thrust using methods previously described (Vaillant et al, 2012; Reed et al, 2013; Cao et al, 2013). Thrust duration was fixed at 100ms based upon clinical findings (Hessell et al, 1990; Herzog et al, 1993; Triano, 2001) where thrust durations in the thoracic and lumbar spines are typically less than 150ms and upon animal studies (Pickar and Kang, 2006; Pickar et al, 2007; Reed et al, 2013) where 100ms represents the threshold duration at which a non-linear increase in muscle spindle discharge occurred.…”
Section: Muscle Spindle Activitymentioning
confidence: 99%
“…While preload magnitude and duration interact to modulate muscle spindle activity during the thrust (Reed et al, 2014), preload, thrust duration, and thrust amplitude all appear to have minimal effect on changing the responsiveness of muscle spindles to spinal movement following the thrust (Cao et al, 2013; Reed et al, 2014). Also using a feline model Kawchuk and colleagues found that thrust duration interacts with thrust amplitude toward changing spinal stiffness (Vaillant et al, 2012). In addition, the specific contact site through which the thrust is applied determines whether spinal stiffness changes (Edgecombe et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hypotheses for HVLA-SM's mechanism of action have begun to focus on central neurophysiological interactions due to the nonlocalized nature of HVLA-SM-induced alterations in somatic pain that have been reported. 15,38,40 Determining both underlying neurophysiological HVLA-SM mechanisms and how clinician-controlled mechanical parameters of HVLA-SM delivery may ultimately optimize changes in central somatosensory pain modulation has become a priority in both basic 4,5,8,14 and clinical 6,7,9,10 studies of spinal manipulation. Therefore, we undertook this study as a first step in determining whether there is a relationship between HVLA-SM, thrust duration, and changes in mechanical activation thresholds of thalamic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Basic and clinical studies aimed at determining the relationship between these various mechanical delivery parameters of spinal manipulation and their effects on neurophysiological, biomechanical, and/or patient outcome measures are just beginning to be reported in the literature. [4][5][6][7][8][9][10][11][12][13][14] Once delineated, these findings could markedly improve and eventually optimize the utilization and effectiveness of spinal manipulation.…”
Section: Key Indexing Termsmentioning
confidence: 99%
See 1 more Smart Citation